Coppermine: riesgos de la no concentración - Jáuregui, Kety (2005)
Major greenfield mining projects are usually surrounded by conflict between the mining company and neighboring communities caused as much by the operator’s mistakes as by anti-mining coalitions and other organized groups rallied around sustainable development issues. For four years while preparation work was underway the mining company put into practice several strategies aimed at addressing claims, including participatory workshops all the way to hiring anexpatriate professional expert charged with addressing environmental issues. A few months before the beginning of mine operations however tension peaked. A multi-sector technical commission was set up including government, residents and company representatives. The technical committee has already issued its report on the issue, including recommendations to keep a watchful eye on the company’s operations. In view of such developments, Coppermine must reframe its policies and strategies.